Neobuxbaumia tetetzo size and length of its apical spines in a light gradient under Mimosa luisana, a nurse shrub - Bravo-Mendoza, Mariana; Espinosa-Cantú, Adriana; Castellanos-Vargas, Iván; Cano-Santana, Zenón (Instituto de Ecología, A.C., 2007)
Environmental conditions and resource availability under the canopy of nurse shrubs in xeric ecosystems are not homogeneous and affect growth rate, survivorship and some morphological traits of young cacti plants. We studied the effect of a gradient of photosynthetically active radiation (PAR) on two traits of the columnar cactus Neobuxbaumia tetetzo: (1) individuals height and (2) length of its apical thorns under the nurse shrub Mimosa luisana in the Zapotitlán Salinas Valley, Puebla (Mexico). We found a positive correlation between the length of the apical thorns and the distance from the nurse shrub, as well as between the height of N. tetetzo and the length of apical thorns. Likewise, the correlation between N. tetetzo size and the distance from the nurse shrub was positive. A multiple regression analysis showed that the length of the apical thorns depends on the size of N. tetetzo individuals, but not on the distance from the nurse shrub. Additionally, the sizes of the N. tetetzo individuals were also dependent on distance from the nurse shrub. When N. tetetzo establishes on the periphery of a nurse shrub the recruitment probability is low as a cause of the high radiation level. Likewise, this factor can have a negative effect on the growth rate because high temperatures reduce photosynthetic rates.